STUDI RELASI STRICT PARENTING PADA ANAK USIA DINI TERHADAP POLA PERKEMBANGAN KOMPETENSI SOSIAL ANAK - Syahrial Labaso; Ratna Hestiana; Deis H. Mantulangi (Irfani (e-Journal), 2024)
Strict parenting is a cultural parenting style that is trending to be used in family education today as a consequence of the cultural heritage of family education in the classical era which was inherited and handed down pedagogically to today's parents. Strict parenting is seen as contributing to the process of forming children's social competence. This research uses descriptive qualitative research with a library study approach by collecting library materials that are deemed relevant and in accordance with the themes in this research. The results of this research show that the application of strict parenting carried out by parents towards children causes children to become closed, not/less able to communicate, and not skilled at adapting to new social environments. This is because children are not involved/not involved in making important decisions related to choices in their lives, this has implications for children failing to find the meaningfulness and value of the activities they do and/or do. Children do not have a sense of responsibility for the activities they do, because from the start they feel they are not involved in the decision-making process for the activities they do. Strict parenting produces children as objects and not as subjects who grow and develop in finding their identity. Keywords: Strict Parenting, Social Competence, Children.